Exploring health needs and the double burden of disease in adults attending public health facilities in the Iraqi Kurdistan - Moramarco, Stefania; Cicala, Mariagrazia; Basa, Faiq B.; Akhshirsh, Gorgees S.; Bezenchek, Antonia; Adhama, Rafal S. L.; Azeez, Bayar S.; Qadir, Sivar A.; Salih, Shahla O.; Alhanabadi, Luma H. H.; Fanti, Iuri; Tofiq, Berivan A.; et al. (Frontiers in Public Health, 2025)
ObjectiveWe analyzed the health needs of the adult population accessing public health facilities in the Iraqi Kurdistan, a region facing both demographic and epidemiological transitions while undergoing post-crisis recovery. We investigates the prevalence and distribution of communicable and non-communicable diseases using real-world data from a digital surveillance system.MethodsData collected across public health centers (PHC) were extracted from the KRG-DHIS2 digital health platform. All records from adult patients were coded using the WHO ICD-10. Diagnoses were grouped into: Communicable, maternal, neonatal and nutritional diseases (CMNNDs), Non-communicable diseases (NCDs), Injuries, Ill-defined diseases. Statistical analyses included descriptive statistics, age-related trends and sex-specific comparisons.ResultsA total of 1,040,695 health events were recorded (years 2016–2022) across 96 PHC: 899,173 were classified as either CMNNDs (41.1%) or NCDs (58.9%). Significant sex and age differences were observed across all major diagnostic categories. NCDs were more common in all age groups and increased significantly with age, while CMNNDs predominated among younger adults. Females accounted for 63.4% of all health events and exhibited higher rates of visits for endocrine, genitourinary, and hematologic conditions. Respiratory system diseases were the most common diagnoses across all ages, followed by genitourinary and digestive system diseases.ConclusionThis study provides critical evidence for understanding health service utilization and disease burden in Iraqi Kurdistan, using a real-time digital surveillance system. The findings confirm the presence of a double burden of disease in a population undergoing rapid transition and underscore the need for integrated, age-and sex-sensitive health interventions.